Interaction of the CD43 Sialomucin with the Mycobacterium tuberculosis Cpn60.2 Chaperonin Leads to Tumor Necrosis Factor Alpha Production - Torres-Huerta, Alvaro (Infect Immun, 2017)
Mycobacterium tuberculosis is the causal agent of tuberculosis. Tumor necrosis factor alpha (TNF-α), transforming growth factor β (TGF-β), and gamma interferon (IFN-γ) secreted by activated macrophages and lymphocytes are considered essential to contain Mycobacterium tuberculosis infection. The CD43 sialomucin has been reported to act as a receptor for bacilli through its interaction with the chaperonin Cpn60.2, facilitating mycobacterium-macrophage contact. We report here that Cpn60.2 induces both human THP-1 cells and mouse-derived bone marrow-derived macrophages (BMMs) to produce TNF-α and that this production is CD43 dependent. In addition, we present evidence that the signaling pathway leading to TNF-α production upon interaction with Cpn60.2 requires active Src family kinases, phospholipase C-γ (PLC-γ), phosphatidylinositol 3-kinase (PI3K), p38, and Jun N-terminal protein kinase (JNK), both in BMMs and in THP-1 cells. Our data highlight the role of CD43 and Cpn60.2 in TNF-α production and underscore an important role for CD43 in the host-mycobacterium interaction.